STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA DIMSUMKAKILIMA.ID - Miranda Suryani; Habiburahman Habiburahman (Jurnal Widya, 2024)
This research aims to find out what marketing strategies are more important to increase sales at Dimsumkakilima.id to face the many competitors who are coming. The informants in this research were 2 employees and 8 consumers, consumers were Dimsumkakilima.id customers, consumers were at least 20 years old and over. The analysis method uses IFAS, EFAS analysis and SWOT analysis. Based on the description and discussion that has been presented, several main points can be drawn from the conclusions of the SWOT analysis as well as strategies that can be implemented by Dimsumkakilima.id in an effort to increase sales. Based on the SWOT Matrix diagram above, it is known that Dimsumkakilima.id is in the first tier, where the situation is very favorable. In this quadrant, Dimsumkakilima.id has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be implemented in this condition is to support aggressive growth policies (growth-oriented strategy).